PROGRAM KEMITRAAN MASYARAKAT (PKM) PEMBUATAN ALAT PENGERING RAMAH LINGKUNGAN UNTUK KELOMPOK INDUSTRI KERUPUK RAMBAK DI DUSUN BAYANAN, GESIKAN, GANTIWARNO, KLATEN - Sudarsono -; Yuli Purwanto; Hadi Prasetyo Suseno (LPPM IST AKPRIND Yogyakarta, 2019)
Rambak crackers are familiar to us, because most people make rambak crackers as friends when eating a meal. This shows that rambak crackers have become a part of daily life. Dusun Bayanan, Gesikan, Gantiwarno, Klaten is a village where some of its residents produce rambak crackers. Marketing is done traditionally, some are sold directly in the market or through cooperatives. The Seroja Makmur Cooperative is a place for farmers to gather crackers and discuss how to grow their food industry. More than 10 rambak cracker business actors are incorporated in cooperatives, one of them is Sriwijaya cracker cracker maker. The manufacturing process carried out is still done manually with simple tools because of limited funding to develop the business. Problems faced by rambak cracker makers are very complex, ranging from equipment to marketing and business competition from other regions. But what they really complained about was the drying process of the cut crackers. the key to the long journey of rambak crackers, because if drying is not perfect the frying process will waste cooking oil and not expand. So that this product is not worth selling and just thrown away. An environmentally friendly dryer is a solution for the makers of rambak crackers. By maximizing the heat from the sun it is expected that drying is far more perfect and drying time can be accelerated, so the amount of production can increase. By not using wood fuel or oil, it is also expected to reduce air pollution and the greenhouse effect.